A scientometric analysis of language teacher emotions (2004-2022): spotlight on the impact of the covid-19 pandemic on lte research - Xu, Xinrou; Xie, Xiao; Nimehchisalem, Vahid (Academy Publication, 2023)
Frontline language teachers have experienced anxiety, vulnerability, and emotional burnout as a result of the sudden transition to online teaching due to the COVID-19 pandemic. This study extracted Language Teacher Emotions (LTE) literature from the Scopus database during the period 2000-2022. During the first round of data extraction, 169 relevant documents written in English were identified. Furthermore, the researchers conducted a scientometric analysis using the literature analysis tool, CiteSpace (v.5.8.R3), and employed co-citation techniques involving visualization and text mining. Our results indicate the following: (1) The first LTE publication was released in 2004, followed by a growing number of publications in the first decade. Nevertheless, more studies were published during 2020-2022; (2) The five countries with the highest number of publications were the USA, China, Iran, the UK, and Turkey; (3) According to Author Co-citation Analysis (ACA), the majority of researchers had expertise in language education, teaching methods, educational assessment, teacher education, and applied psychology; (4) Based on the Document Co-citation Analysis (DCA), emotional labour, emotional burden, and vulnerability were the primary topics of interest; (5) Cluster analysis of keywords indicates that the LTE research trajectory was inevitably affected by the COVID-19 pandemic. As the first scientometric review of LTE research, this study calls for a greater understanding of the impact of online and blended teaching during the post-pandemic period. It will be of interest to inter-domain researchers and frontline teachers in terms of identifying influential scholars, publications, and research trends, as well as considering future research projects.